Changes in Proteomic Profiles are Related to Changes in BMI and Fat Distribution During 10 Years of Aging. Issue 1 (5th December 2019) - Lind, Lars; Figarska, Sylwia; Sundström, Johan; Fall, Tove; Ärnlöv, Johan; Ingelsson, Erik
Abstract : Objective: This study investigated how changes in 84 proteins over a 10‐year period of aging were related to changes in measures of body fat and distribution over the same period. Methods: Cardiovascular candidate proteins were measured using the proximal extension assay technique, along with BMI and waist‐hip ratio (WHR), at ages 70, 75, and 80 in 1, 016 participants of the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) cohort. Associations of changes in plasma protein levels, BMI, and WHR over time were analyzed using linear mixed models. Results: Changes in 19 and 16 proteins were significantly associated with changes in BMI and WHR, respectively ( P < 0.00059), over the investigated 10‐year period. Leptin and fatty acid‐binding protein 4 were among the proteins most strongly associated with changes in both BMI and WHR. Four of the proteins significantly tracked with change in BMI ( P < 0.00059) but not WHR ( P > 0.05): endothelial cell‐specific molecule 1, pentraxin‐related protein PTX3, ST2 protein (also known as interleukin‐1 receptor‐like 1), and spondin‐1. Five proteins tracked with change in WHR ( P < 0.00059) but not BMI ( P > 0.05): caspase‐8, cathepsin L1, oxidized low‐density lipoprotein receptor 1, interleukin‐6 receptor subunit alpha, and C‐C motif chemokine 20. Conclusions: This is the first large longitudinal study of how changes in plasma protein signatures are associated with changes in measures of body fat and distribution over 10 years of aging.